Risk Perception in the Internationalization of Brazilian Companies: An Analysis in Different Entry Modes - Santos Jhunior, Ronaldo de Oliveira; Abib, Gustavo; Stocker, Fabrício (Organizations and Markets in Emerging Economies, 2021)
The existence of risks is a premise in business-related matters, mainly in the exploration of international opportunities. Organizations seeking to operate abroad are potentially more susceptible to the risks that exist internationally. This study follows the behavioral approaches to internationalization and conceptual ideas about risk and risk perception in international business. The main goal is to understand how the risk perception of managers in Brazilian companies with different entry modes is configured. In this qualitative research, a multiple case study was carried out. The data collection techniques established were the analysis of documents and the performance of semi-structured interviews with managers responsible for the internationalization processes of six Brazilian companies. Regarding the risks inherent to these processes, there was a greater emphasis on country/political risk factors, followed by monetary risk. The risks perceived with greater evidence, considering the entry modes addressed, are also presented for a better understanding of the results.